2020
DOI: 10.1001/jamanetworkopen.2020.26373
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Association of Construction Work With Risks of COVID-19 Infection and Hospitalization in Texas

Abstract: Key Points Question Is construction work associated with increased community transmission of coronavirus disease 2019 (COVID-19) and disproportionate morbidity among construction workers in US cities? Findings This decision analytical model of COVID-19 found that resuming construction work during shelter-in-place orders was associated with increased hospitalization risks in the construction workforce and increase transmission in the surrounding community. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 21 publications
1
61
0
1
Order By: Relevance
“…In fact, a recent investigation from Los Angeles concluded that construction workers were reporting the highest number of positive cases compared to workers in other industries, including transportation, healthcare, and manufacturing [ 18 ]. Likewise, another study found evidence that construction workers are roughly five times more likely to be hospitalized as a result of COVID-19 than workers in other industries [ 19 ]. Several other state public departments have also highlighted the risk of COVID-19 infections, particularly among the construction workforce [ 20 , 21 , 22 ].…”
Section: Introduction and Study Motivationmentioning
confidence: 99%
“…In fact, a recent investigation from Los Angeles concluded that construction workers were reporting the highest number of positive cases compared to workers in other industries, including transportation, healthcare, and manufacturing [ 18 ]. Likewise, another study found evidence that construction workers are roughly five times more likely to be hospitalized as a result of COVID-19 than workers in other industries [ 19 ]. Several other state public departments have also highlighted the risk of COVID-19 infections, particularly among the construction workforce [ 20 , 21 , 22 ].…”
Section: Introduction and Study Motivationmentioning
confidence: 99%
“…Also, although social distancing in the construction workplace can hardly be implemented, still it should be practiced for an effective social distancing, according to the hospitalization risk is expected to be two to three times higher for construction workers than nonconstruction workers [11].…”
Section: Challenges Experienced As Construction Workersmentioning
confidence: 99%
“…[1][2][3][4] Among undocumented immigrants, high infection rates are driven in part by high participation in frontline occupations such as construction, manufacturing, and wholesale trade associated with workplace outbreaks, crowded households, and exclusion from health insurance coverage and unemployment benefits. 5,6 Language barriers, fear of medical bills, limited familiarity with the health system, and concern about immigration can dissuade undocumented immigrants from seeking help. 3,7,8 Latinxs account for only 5.5% of the Baltimore City population, but they are fastest growing ethnic group in the city.…”
Section: Introductionmentioning
confidence: 99%